Pelatihan Kursus Menjahit Singkat di Lembaga Kesejahteraan Sosial Anak (LKSA) A s-Shohwah Yatim dan Piatu Pekanbaru - Nelsi Arisandy; Sahwitri Triandani; Irien Violinda Anggriani (Asosiasi Dosen Akuntansi Indonesia, 2022)
This short sewing course training was held at the LKSA (Child Social Welfare Institution) As-Shohwah orphans and orphans Pekanbaru with young women as participants. About 30 children and young women live here, most of whom are still of school age. This training aims to measure the level of parental understanding of entrepreneurship and conduct training in sewing clothes, skirts, pillowcases, and sheets during the planned time span, which is two days.